Beyond feminist aesthetics: Feminist literature and social change - Felski, Rita (Harvard University Press., 1989)
Beyond Feminist Aesthetics has a dual focus. First, Rita Felski gives a critical account of current American and European feminist literary theory, and second, she offers an analysis of contemporary fiction by women, drawing in particular on the genres of the autobiographical confession and the novel of self-discovery, in order to show that this literature raises questions for feminism that cannot be answered in terms of a purely gender based analysis. Felski argues that the idea of a feminist aesthetic is a nonissue that feminists have needlessly pursued; she suggests, in contrast, that it is impossible to speak of “masculine” and “feminine,” “subversive” and “reactionary” literary forms in isolation from the social conditions of their production and reception. The political value of such works of literature from the standpoint of feminism can be determined only by an investigation of their social functions and effects in relation to the interests of women in a particular historical context. This leads her to argue for an interdisciplinary approach to the analysis of literature which can integrate literary and social theory, and to develop such an approach by drawing upon the model of a feminist counter-public sphere. Rita Felski has produced a closely reasoned, stimulating book that creates a new framework for discussing the relationship between literature and feminist politics. It will interest students and teachers of women’s studies, comparative literature, cultural studies, and fiction.
Keywords: 1900-1999; changement social; cours; discipline; fem1000; occident; premier cycle; périodes historiques; thématiques; écriture des femmes*; études littéraires

Toute écriture est amour - Gagnon, Madeleine; Verthuy, Maïr.; Maranda, Jeanne (VLB, 1989)
Depuis Les Mots vivants en 1969, Madeleine Gagnon a publié plusieurs livres importants dont Lueur, Les Fleurs du Catalpa et Femmeros. Madeleine Gagnon a colligé, dans Autographie I, des textes de fiction publiés entre 1969 et 1981. Autographie II rassemble les textes de réflexion et critiques écrits parallèlement à son œuvre de fiction.
Section: 1 v. (193 p.) ; 23 cm
Keywords: 1900-1999; amériques; arts; canada; cours; discipline; lit3220; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Malaise et révolte des femmes dans la littérature québécoise depuis 1945 - Saint-Martin, Lori; Université Laval Groupe de recherche multidisciplinaire féministe (Groupe de recherche multidisciplinaire féministe, Université Laval, 1989)
Section: xxxvi, 373 pages : illustrations ; 28 cm
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; amériques; arts; canada; cours; discipline; lit3495; premier cycle; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires

Woman, native, other: Writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press., 1989)
"" ... Methodologically innovative ... precise and perceptive and conscious ... ""–Text and Performance Quarterly""Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color.""–Chandra Talpade Mohanty""The idea of Trinh T. Minh-ha is as powerful as her films ... formidable ... ""–Village Voice"" ... its very forms invite the reader to participate in the effort to understand how language
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; fem1000; fem3200; féminisme décolonial; littérature; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires

Woman, native, other: writing postcoloniality and feminism - Trinh, T. Minh-Ha (Indiana University Press, 1989)
" . . . methodologically innovative . . . precise and perceptive and conscious . . . " —Text and Performance Quarterly "Woman, Native, Other is located at the juncture of a number of different fields and disciplines, and it genuinely succeeds in pushing the boundaries of these disciplines further. It is one of the very few theoretical attempts to grapple with the writings of women of color." —Chandra Talpade Mohanty "The idea of Trinh T. Minh-ha is as powerful as her films . . . formidable . . . " —Village Voice " . . . its very forms invite the reader to participate in the effort to understand how language structures lived possibilities." —Artpaper "Highly recommended for anyone struggling to understand voices and experiences of those 'we' label 'other'." —Religious Studies Review Audio book narrated by Betty Miller. Produced by Speechki in 2021.
Keywords: 1900-1999; approches et analyses; arts; cours; discipline; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; premier cycle; périodes historiques; ressource en ligne; thématiques; écriture des femmes*; études littéraires